Facial emotion recognition in patients with subjective cognitive decline and mild cognitive impairment. (17th September 2015) - Pietschnig, J.; Aigner-Wöber, R.; Reischenböck, N.; Kryspin-Exner, I.; Moser, D.; Klug, S.; Auff, E.; Dal-Bianco, P.; Pusswald, G.; Lehrner, J.
ABSTRACT: Background: Deficits in facial emotion recognition (FER) have been shown to substantially impair several aspects in everyday life of affected individuals (e.g. social functioning). Presently, we aim at assessing differences in emotion recognition performance in three patient groups suffering from mild forms of cognitive impairment compared to healthy controls. Methods: Performance on a concise emotion recognition test battery (VERT-K) of 68 patients with subjective cognitive decline (SCD), 44 non-amnestic (non-aMCI), and 25 amnestic patients (aMCI) with mild cognitive impairment (MCI) was compared with an age-equivalent sample of 138 healthy controls all of which were recruited within the framework of the Vienna Conversion to Dementia Study. Additionally, patients and controls underwent individual assessment using a comprehensive neuropsychological test battery examining attention, executive functioning, language, and memory (NTBV), the Beck Depression Inventory (BDI), and a measure of premorbid IQ (WST). Results: Type of diagnosis showed a significant effect on emotion recognition performance, indicating progressively deteriorating results as severity of diagnosis increased. Between-groups effect sizes were substantial, showing non-trivial effects in all comparisons (Cohen's d s from −0.30 to −0.83) except for SCD versus controls. Moreover, emotion recognition performance was higher in women and positively associated with premorbid IQ. Conclusions: Our findings indicate substantial effects of progressive neurological damage on emotion recognition in patients. Importantly, emotion recognition deficits were observable in non-amnestic patients as well, thus conceivably suggesting associations between decreased recognition performance and global cognitive decline. Premorbid IQ appears to act as protective factor yielding lesser deficits in patients showing higher IQs.